Prognosis of Infantile Spasms - J Gordon Millichap (Pediatric Neurology Briefs)
The developmental, neurologic, and seizure outcome and prognostic factors of 57 cases of infantile spasms were evaluated in relation to etiology (cryptogenic 17 cases, symptomatic 40 cases) at the Hospital for Sick Children, Toronto, Canada.